PARAFFIN SEPARATION VACUUM DISTILLATION - Zaid A. Abdulrahman (Tikrit Journal of Engineering Sciences, 2013)
Simulated column performance curves were constructed for existing paraffin separation vacuum distillation column in LAB plant (Arab Detergent Company/Baiji-Iraq). The variables considered in this study are the thermodynamic model option, top vacuum pressure, top and bottom temperatures, feed temperature, feed composition & reflux ratio. Also simulated columns profiles for the temperature, vapor & liquid flow rates composition were constructed. Four different thermodynamic model options (SRK, TSRK, PR, and ESSO) were used, affecting the results within 1-25% variation for the most cases. The simulated results show that about 2% to 8 % of paraffin (C10, C11, C12, & C13) present at the bottom stream which may cause a problem in the LAB plant. The major variations were noticed for the top temperature & the  paraffin weight fractions at bottom section with top vacuum pressure. The bottom temperature above 240 oC is not recommended because the total bottom flow rate decreases sharply, where as  the weight fraction of paraffins decrease slightly. The study gives evidence about a successful simulation with CHEMCAD